Delinquent networks in Sweden - Sarnecki, Jerzy (Journal of quantitative criminology, 1990)
This study covers all persons under the age of 20 who were suspected of having committed a crime in the Swedish city of Borlänge (approx. 50,000 inhabitants) during the years of 1975–1977. The juveniles (575 in all) were followed up during a total of 10 years. A sociometric method based on police data was developed for studying co-offending patterns. The method was validated through a smaller number of interviews with the juveniles. This study shows that a large majority of the most delinquency active juveniles was associated with a large network of delinquent relations. The stronger the connection to this network, the more substantial, serious, and long-lasting were the delinquency and other asociality. This network also seemed to be very important with regard to the reproduction of juvenile delinquency in the municipality. At the end of the follow-up period juvenile delinquency in Borlänge had basically the same character as at the beginning, even though the juveniles included in the network were, to a large extent, new. The young offenders who were central figures in the new network had successively learned their roles from the network's old members.